Capital Flows, Financial Integration, and International Reserve Holdings : The Recent Experience of Emerging Markets and Advanced Economies - Sharma, Sunil (IMF Working Papers; Working Paper, 2007)
This paper examines the interaction between capital flows and international reserve holdings in the context of increasing financial integration. For emerging markets the sensitivity of reserves to net capital flows was negative in the 1980s, but became positive after the Asian crisis when these countries used net capital flows to build up reserves. For advanced countries, net capital flows had a negative effect on reserves, especially in recent years. Using measures of financial globalization, we also provide evidence that the sensitivity of reserves to net capital flows increased with globalization for emerging markets while it decreased for advanced countries.